Virtual Clothing Display Platform Based on CLO3D and Evaluation of Fit (Journal of Fiber Bioengineering and Informatics, 2023)
The article uses CLO3D and HTML5 to design a virtual clothing display system. And for the problemsthat may arise when using CLO3D to make garments, the solution is given. At the same time, theevaluation of the fit of the virtual clothing made in CLO3D was discussed. Designers can use CLO3D toquickly create virtual clothing in accordance with the users' requirements. After, through the system,designers can publish it on the Web for the users to effectively see the process of cloth making in anall-rounded way, while sustaining communication with designers. The design of this virtual clothingdisplay platform provides some reference value for the digital model of the apparel industry.